All together now: Cooperative classroom climate and the development of youth attitudes toward immigrants. Issue 177 (15th April 2021) - Miklikowska, Marta; Eckstein, Katharina; Matera, Joanna
Abstract: Although classrooms have been described as an important socialization agent for the development of intergroup attitudes, the role of classroom climate has rarely been investigated. This 5‐wave study of Swedish adolescents ( N = 892, 51.1% girls, nested in 35 classrooms) examined the role of cooperative classroom climate for the development of youth attitudes toward immigrants. The results of multilevel analyses showed that adolescents who perceived classroom climate to be more cooperative had lower levels of anti‐immigrant attitudes compared to youth who perceived the classroom climate as less cooperative. Similarly, classrooms with a more cooperative climate were more positive toward immigrants than classrooms with a less cooperative climate. In addition, cooperative classroom climate did not moderate the effects of classroom ethnic diversity on youth attitudes. These findings suggest that cooperative classroom climate reduces the risk of prejudice development.